Changes in anterior temporal and posterior medial hippocampal network connectivity in Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Dautricourt, Sophie; de Flores, Robin; Landeau, Brigitte; Poisnel, Géraldine; Vanhoutte, Matthieu; Delcroix, Nicolas; Vivien, Denis; De la Sayette, Vincent; Chetelat, Gael
Abstract: Background: Hippocampal connectivity is affected early in Alzheimer's disease and plays a crucial role in episodic memory dysfunction. Different hippocampal subnetworks have been identified, namely the anterior temporal (AT) and the posterior medial (PM) networks that are specifically related to separate subregions of the medial temporal lobe (MTL) thought to be differentially affected in AD. The aim of this study was to assess the specific connectivity of these two networks and its changes in Alzheimer's disease, using both a cross‐sectional and a longitudinal approach. Method: Fifty‐three cognitively impaired patients on the Alzheimer's continuum with mild cognitive impairment or dementia, all amyloid‐β (Aβ)‐positive, and 68 Aβ‐negative cognitively unimpaired elderly controls were included. They underwent structural T1‐MRI and resting‐state functional MRI (fMRI) scans at baseline and at 18‐month follow‐up as well for 30 patients. Seed‐based analyses were performed, using individual automatic segmentation of MTL subregions as seeds, to assess the functional connectivity within the AT (from the perirhinal cortex and anterior hippocampus seeds) and the PM (from the parahippocampal cortex and posterior hippocampus seeds) networks. First, we compared the functional connectivity of the two networks within the controls to highlight their specificities. Second, we compared MTL subregion connectivity within each network between groups, and between baseline and follow‐up in the patients, to assess AD‐related changes compared to controls and over time. Result: AT and PM networks showed distinct connectivity patterns in controls (Fig. 1). Patients showed decreased connectivity between the anterior hippocampus and regions of the PM network, and increased connectivity between anterior MTL subregions, compared to controls (Fig. 2). Over the 18‐month follow‐up period, decreased connectivity was found between both the anterior and posterior hippocampus and regions of the PM network, while increased connectivity was observed between several anterior MTL subregions and regions of the AT network (Fig. 3). Conclusion: AD is characterized by both decreased MTL connectivity with the PM hippocampal network and increased connectivity with the AT hippocampal network. The specific assessment of the two main hippocampal subnetworks shed light on the overall pattern of AD‐related hippocampal changes involving both connectivity default and possible compensation or erroneous hyperactivity patterns.